Pengaruh Motivasi Perjalanan dan Sikap Wisatawan Terhadap Niat Berkunjungan Kembali ke Kawasan Wisata Jatigede - Sri Utari; Gilang Pratama Putra; Ahmad Hudaiby Galih Kusumah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines how the variables of travel motivation and tourist attitudes influence the intention to revisit the Jatigede tourist area. This study aims to determine the extent to which travel motivation (X), tourist attitudes (Y) affect the intention to visit again (Z). The research method used is a survey using a questionnaire as a data collection tool. The sample used in this study were 205 tourist respondents who had visited the Jatigede tourist area. The data analysis technique uses PLS-SEM analysis with the Smart PLS 4 program. The results of this study indicate that travel motivation has no direct influence on the intention to revisit. Travel motivation has a direct influence on tourist attitudes. Tourist attitudes have a direct influence on revisit intentions. Also, tourist attitudes mediate the effect of travel motivation on revisit intentions.